Some Types of Nano Penta Regular Spaces - Hilal, Anaam M; Yaseen, Rana B (Journal for Research in Applied Sciences and Biotechnology, 2024)
The goal of our study is to obtain a new space, which we called the Nano Penta regular space, by studying three cases independent of each other in terms of the number of equivalence relationships for the universe set and its subset. Its properties and its relationship to some Nano Penta separation axioms were discussed and the strongly NpNp-Regular space and its relationship to the Nano Penta regular space was studied.